Integrating strategic planning intentions into land-change simulations: Designing and assessing scenarios for Bucharest. (January 2022) - Bacău, Simona; Domingo, Darío; Palka, Gaëtan; Pellissier, Loïc; Kienast, Felix
Highlights: In Bucharest, future land-use demands can be met regardless of the scenario. Simulations integrating planning show a non-sustainable loss of agricultural areas. The mismatch between planning goals and demands produces high land consumption. The method of translating strategic intentions is useful for assessments worldwide. Abstract: Urban regions worldwide revert to scenario-based simulations to understand and cope with uncertain land-use changes and future land-use demands. Whereas scenarios account for a variety of driving forces to simulate land change, spatial planning has received limited attention. To improve understanding of the potential contribution of planning to urban land change, we developed and simulated scenarios of development for Bucharest, addressing the local scale, and Bucharest-Ilfov Development Region, addressing the regional scale. The designed scenarios reflect (i) expected future land-use demands for living space, built-up areas, green space and agricultural areas, and (ii) statutory and strategic planning intentions extracted from four spatial plans and weighted based on expert opinion. All scenarios, alongside natural and socioeconomic driving forces, were simulated for both the local and the regional scales using the CLUMondo land-change model. Findings show that all future demands can be met under all scenarios, but that planning will make little contribution. Moreover, simulations highlight that integrating strategic planning intentions would produce a higher loss of agricultural lands than simulations with statutory planning intentions. Consequences of our findings for the role of planning in driving land change at various scales in multi-level planning systems are discussed.